MicroRNAs as novel biomarkers for the diagnosis and treatment of pediatric diseases - Hwal Rim Jeong; Il Tae Hwang (The Korean Pediatric Society, 2024)
MicroRNAs (miRNAs) are highly conserved noncoding RNAs that regulate gene expression by silencing or degrading messenger RNAs. Many of the approximately 2,500 miRNAs discovered in humans are known to regulate vital biological processes, including cell differentiation, proliferation, apoptosis, and embryonic tissue development. Aberrant miRNA expression may have pathological and malignant consequences. Therefore, miRNAs have emerged as novel diagnostic markers and potential therapeutic targets for various diseases. Children undergo various stages of growth, development, and maturation between birth and adulthood. It is important to study the role of miRNA expression in normal growth and disease development during these developmental stages. In this mini-review, we discuss the role of miRNAs as diagnostic and prognostic biomarkers in various pediatric diseases.